Mediating effect of happiness in the relationship between positive childhood experiences and social media addiction in young adults - Öztekin, Gülçin Güler (Journal of Dependence, 2024)
Objective: This study focuses on exploring the connection between positive experiences during childhood, overall happiness, and the propensity for social media addiction in young adults.Method: The study gathered data from 413 young adults in Turkey, averaging 25.73 years in age (Standard Deviation=4.77). Data collection involved using the Positive Childhood Experiences Scale, the Oxford Happiness Questionnaire, and the Social Media Addiction Scale. Mediation analysis was performed to examine the mediating effect of happiness.Results: Positive childhood experiences were positively associated with happiness and negatively associated with social media addiction. There was a negative relationship between happiness and social media addiction. Happiness played a mediating role in the relationship between positive childhood experiences and social media addiction.Conclusion: Participants with favorable experiences in childhood reported higher levels of happiness and less social media addiction. These results suggest that the social media addiction prevention and intervention programs should focus efforts on enhancing happiness and positive childhood experiences.
Keywords: Positive childhood experiences; happiness; social media addiction; young adults